Analisis Kestabilan Model SITR pada Penyebaran Penyakit Hepatitis A dengan Vaksinasi - Sidik, Amelia Tri Rahma; Sari, Lia Nanda; Ismail, Apon (Scimadly Publishing, 2022)
In this article, the SITR Model for the spread of Hepatitis A by Vaccination is discussed. This study aims to analyze the stability of the model for the spread of hepatitis A disease around the points, interpret the model that has been formed by performing numerical simulations, and determine the effect of vaccination and treatment on the human population infected with hepatitis A. indicated by (T1) is stable and the endemic fixed point indicated by (T2) is stable. Based on the simulation obtained from each class (S, I, T, R) for R0<1, it shows that the population dynamics is (0.13,0,0,0.87) of the total population. Meanwhile, for R0>1 with a basic reproduction number, it shows the population dynamics of each class (S, I, T, R) that is (0.12,0.0056,0.0053,0.85) of the total population.